1994
DOI: 10.1089/neu.1994.11.507
|View full text |Cite
|
Sign up to set email alerts
|

Traumatically Induced Altered Membrane Permeability: Its Relationship to Traumatically Induced Reactive Axonal Change

Abstract: Recent studies have suggested that severe forms of traumatic brain injury (TBI) can be associated with direct alterations of the axolemma. The present study evaluated whether injuries of mild to moderate severity are associated with comparable change. To this end, we used extracellular horseradish peroxidase (HRP) to determine if altered axolemmal permeability occurred following the traumatic event. Adult cats received intrathecal infusions of peroxidase and then were prepared for mild to moderate fluid percus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(158 citation statements)
references
References 21 publications
5
153
0
Order By: Relevance
“…In surviving animals, from the 5 th min. post injury, compacted axons can be demonstrated by the uptake of intraventricularly administered horseradish peroxidase (Pettus et al, 1994), and from the 15 th min. on by Ab-38 and RMO-14 immunohis- Fig.…”
Section: Comments On the Methods Used And The Results Obtainedmentioning
confidence: 99%
See 1 more Smart Citation
“…In surviving animals, from the 5 th min. post injury, compacted axons can be demonstrated by the uptake of intraventricularly administered horseradish peroxidase (Pettus et al, 1994), and from the 15 th min. on by Ab-38 and RMO-14 immunohis- Fig.…”
Section: Comments On the Methods Used And The Results Obtainedmentioning
confidence: 99%
“…The in vivo formation of compacted axons scattered among normal axons was discovered a decade ago in experimental animals that survived for 5 min. or longer following a head injury (Pettus et al, 1994). Shorter survival periods were not investigated.…”
Section: Comments On the Methods Used And The Results Obtainedmentioning
confidence: 99%
“…On the other hand, axons that undergo dynamic deformation but do not swell may nonetheless suffer subtle yet important pathophysiological changes, including an increase in intra-axonal calcium and sodium concentrations or mitochondrial dysfunction, as suggested by previous in vivo and in vitro studies Pettus and Povlishock, 1996;Pettus et al, 1994;Smith et al, 1999b;Staal et al, 2010;Wolf et al, 2001;Yuen et al, 2009). These processes are thought to contribute to physiological dysfunction of white matter pathways, such as the reduction in conduction velocity that has been observed in mTBI (Baker et al, 2002;Kumar et al, 2009;Nuwer et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Arrows, in A, indicates that the cells were still proliferating (cells with round cell bodies) and not differentiated. Differentiated cells (B) have grown in small aggregates, and they have formed small neuronal nets at 7 th day of seeding (Pittman et al, 1993;Das et al, 2004) Pettus, et al (1994); specifically, the increased membrane permeability to macromolecules found in moderate to severe injury. Based on the previously demonstrated loading-rate dependence of cell injury, we varied loading rate over a wide range.…”
Section: Injury Protocolmentioning
confidence: 99%
“…The immediate structural consequences of the mechanical deformation of neurons during TBI remain poorly characterized, and the mechanisms by which the mechanical stimulus gives rise to both acute biochemical responses and delayed pathology are not known. The loss in cell membrane integrity and plasma membrane modifications, including membrane blebbing and altered permeability, have recently been found to be the major contributors to the development of neuronal damage subsequent to traumatic injury by leading to ionic imbalances and activation of several cellular pathways (Geddes et al, 2003;LaPlaca and Thibault, 1998;Obrenovitch and Urenjak, 1997;Pettus et al, 1994). In this paper, we describe the development of an in vitro model to study the relationship between mechanical loading parameters and injury severity and to elucidate the role of acute membrane damage in subsequent pathology.…”
Section: Introductionmentioning
confidence: 99%